Dual‐band circularly polarised planar monopole antenna for WLAN/Wi‐Fi/Bluetooth/WiMAX applications. Issue 6 (26th March 2018) - Li, Qian; Wei, Yanyu; Ding, Chong; Tan, Mingtao; Zhang, Luqi; Lei, Xia; Wu, Gangxiong; Wang, Zhanliang; Lu, Zhigang; Gong, Yubin
Abstract : A novel planar monopole antenna with dual‐band circularly polarisation (CP) is presented here. The antenna consists of a modified L‐shaped monopole, an inverted‐L strip, and a modified ground. The utilisation of the modified L‐shaped monopole not only generates dual‐band operation, but also excites CP radiation in the lower band. In order to achieve CP in the upper band, a parasitic inverted‐L strip is added on the top plane of the substrate and a modified ground is designed. The proposed antenna has been fabricated and tested, the measured −10 dB reflection coefficient bandwidths are 370 MHz (2.38–2.85 GHz) in the lower band and 2330 MHz (4.05–6.38 GHz) in the upper band. The measured corresponding 3 dB axial ratio (AR) bandwidths are 610 MHz (2.39–3 GHz) and 850 MHz (5.15–6 GHz), respectively. The overlapped −10 dB reflection coefficient and AR bandwidths can totally cover the WLAN bands, Wi‐Fi bands, Bluetooth band, and partly cover the WiMAX bands. The proposed antenna owns bidirectional radiation characteristic and reasonable gain at both the lower band and the upper band.